Bushido : the samurai code of Japan - Nitobe, Inazō, 1862-1933 (Tuttle Publishing, 2018)
Bushido: the samurai code of Japan is one of the most influential books ever written on "the way of the warrior." A classic study of Japanese culture, the book outlines the moral code of the samurai way of living and the virtues every warrior holds dear. In Bushido, Nitobe points out similarities between Western and Japanese history and culture. He argues that "no matter how different any two cultures may appear to be on the surface, they are still created by human beings, and as such have deep similarities." Nitobe believed that connecting Bushido with greater teachings could make an important contribution to all humanity, that the way of the samurai is not something peculiarly Japanese, but of value to the entire human race.